Faktor Penghambat Kedisiplinan Mahasiswa Terhadap Proses Pembelajaran di Kampus - Antonius A. Saetban (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study is to find out how students manage lecture time in completing lecture assignments. The benefit is to help students make the most of their time as well as input for institutions, in this case the Tribuana Kalabahi University campus, to design programs related to disciplinary issues in providing assistance and guidance to students. Furthermore, the method used in this research is descriptive-qualitative to describe a symptom, event, and event that occurs factually, systematically, and accurately. The location of this research took place on the Tribuana Kalabahi University Campus with a total of 75 respondents. Fourth semester students of the Elementary School Teacher Education Study Program. Research data shows that students' inability to study discipline is evidenced by the answers of respondents, namely, 85% of respondents answered that the inhibiting factors came from the students themselves. Apart from internal inhibiting factors, there are also external inhibiting factors. 53% of respondents answered that they had external barriers for the following reasons: Influence of friends, lack of family support, having side jobs, working a lot at home, feeling comfortable relaxing with friends rather than spending time studying.